Geopolitics and trade in the euro area and the United States: De-risking of import supplies? - Ivelina Ilkova; Laura Lebastard; Roberta Serafini (European Central Bank (ECB), 2024)
Based on granular data at the product level, this paper looks at whether and how the euro area and the United States have modified their import sourcing strategies since 2016, the role played by geopolitical tensions and the potential impact on import prices. It considers two different, but not mutually exclusive, changes to sourcing strategies for a given product: (i) increasing the number of sourcing countries and (ii) reducing the import market share of the main supplier country. Data suggest that both regions have, on average, increased the number of sourcing countries, particularly for products that are mostly imported from "geopolitically distant" countries (based on UN General Assembly voting records). Broadening the number of supplier countries has come at a cost; however, it has affected only a small share of total imports, with modest implications for inflation and the terms of trade. At the same time, evidence of a reduction in the import share of the main supplier country is more mixed and is generally associated with a shift towards cheaper - but not necessarily geopolitically closer - countries, suggesting that cost considerations take precedence over supply chain resilience and national security concerns.
Keywords: F14; F51; F62; 330; fragmentation; diversification; rebalancing; geopolitics; euro area; international trade; import (EU); supply; United States